Role komunikacyjne nadawcy w Drodze do nieba ks. Ludwika Skowronka - Dylus, Daniela (Forum Lingwistyczne, 2015)
The Communicative Role of the Sender in On Way to Heaven by rev. Ludwik Skowronek On Way to Heaven by rev. Ludwik Skowronek is the indication of the author’s concern to preserve the traditional model of a family. Consequently so, Christian families are aimed to be the main recipients of the text. The Skowronek’s text edited as a prayer book in Silesia in early decades of the 20th century is devoted to the subject of a family within the church community. The thorough analysis of the text allows the reader to see the coexistence of the evident persuasion with different ways of soothing the direct didactic. By predetermining the shape of the sender-receiver relation, the impressive function of language reveals asymmetrical character of the roles which the participants of the speech act can take. Key words: persuasion, On Way to Heaven, sender-receiver relation, religious language, Silesia, rev. Skowronek